Navigating hardship - Perger, Nina (Annales. Series historia et sociologia, 2025)
This article analyses the practical strategies used by older people living in poverty to navigate their social worlds, which, applying Pierre Bourdieu’s theoretical framework, are framed by "positional suffering" due to low social status. Qualitative data gathered from biographical interviews reveal strategies that include adjusting one’s aspirations to what is attainable, adapting one’s needs to match necessities, learned self-sufficiency, relentless prioritisation, an emphasis on cost-consciousness and stringent conservation, prioritisation by sacrifice and dispositions to "make something out of nothing". Crucially, these strategies emphasise that older people living in poverty are active agents navigating through hardship.
Keywords: elderly; habitus; habitus of necessity; old age; poverty; practical strategies; praktične strategije; revščina; starejše ženske; stari ljudje; starost